Henry Clay family papers - Clay, Henry, 1777-1852.; Clay, James B. (James Brown), 1817-1864.; Morrison, James, 1755-1823.
Personal, official, and family correspondence, speeches, writings, business records, legal files, biographical material, printed matter, and other papers chiefly documenting the public career and private life of statesman Henry Clay (1777-1852), U.S. secretary of state and representative and senator from Kentucky; and his son, James B. Clay (1817-1864), diplomat, U.S. representative from Kentucky, and Confederate sympathizer; and other members of Henry Clay's family.
Part I consists of general correspondence mainly relating to politics, dispatches and instructions sent by Henry Clay as secretary of state to chargés d'affaires and ministers plenipotentiary, and other papers. Topics include the Burr conspiracy; Clay's duels with Humphrey Marshall and John Randolph; the War of 1812, peace negotiations, and the Treaty of Ghent (1814); tariff, public lands, internal improvements, and other postwar domestic issues; relations with South America; presidential politics, particularly the elections of 1824, 1832, 1844, and 1848 in all of which Clay was a Whig candidate or nominee; Clay's opposition to the politics of Andrew Jackson; the rechartering of the Bank of the United States; the nullification crisis; slavery in the District of Columbia; the annexation of Texas; and the influence of New York politics and the Liberty Party on the election of 1844.
Prominent correspondents in Part I include James Brown, Francis Taliaferro Brook, and Josiah Stoddard Johnston. Other correspondents include John Quincy Adams, Nicholas Biddle, Francis Preston Blair, Horace Greeley, William Henry Harrison, Christopher Hughes, Amos Kendall, the marquis de Lafayette, John L. Lawrence, John Marshall, James Monroe, Peter B. Porter, William Beatty Rochester, Richard Rush, John Sargeant, Zachary Taylor, Daniel Webster, and Robert Wickliffe.
Part II consists of correspondence, notes, memoranda, journals, speeches, and other papers of Henry Clay's mother Elizabeth Hudson Clay Watkins, brothers Porter and John Clay, father-in-law Thomas Hart, wife Lucretia Hart Clay, children Theodore Wythe Clay, Anne Brown Clay Erwin, Henry Clay, Jr., and James B. Clay, and grandchildren. Also included are client files and other legal papers from the law offices of Henry Clay, Thomas Hart, and James B. Clay in Lexington, Ky.
Part II also contains correspondence, speeches, and writings of James B. Clay relating to his diplomatic service in Portugal, support of James Buchanan in the election of 1856, his congressional career as a Whig, border wars in Kansas, the unsuccessful peace convention of 1861, and blockade-running, Braxton Bragg's campaign in Kentucky, and other Civil War topics. Papers of his sons include correspondence of James Brown Clay, Jr., aide-de-camp to Gen. John C. Breckinridge, relating to Civil War military life and campaigns; journal (1878) of Thomas Jacob Clay describing U.S. Cavalry forays against Mexicans and Indians while stationed at Fort Clark, Tex.; and correspondence and writings (1880-1884) of Henry ("Harry") Clay relating to his participation in the Arctic expeditions of A. W. Greely and Henry W. Howgate. Also includes a biography of Henry Clay and other writings by James B. Clay's wife, Susan Maria Jacob Clay, and religious and fictional writings by Lucretia Hart Clay.
Also included in Part II are the papers of James Morrison (1755-1823) include correspondence and records relating to his work as a contractor for the army during the War of 1812 and president of the Lexington branch of the Bank of the United States and to the settlement of his estate for which Henry Clay was executor. Morrison's papers also include those of George Nicholas (1754?-1790) for whom Morrison was executor. Financial records (1829-1868) of Transylvania University, a beneficiary of Morrison's estate, are also included.
Microfilm edition of the papers of Henry Clay in this and other collections in the Library of Congress Manuscript Division cataloged in record 97-185283. The microfilm was produced in 1957 by the National Archives under the auspices of the National Historical Publications Commission, nos. 13,707-22N (13,789-22P), 13,789.1-1N-1P and 17,343-1N-1P.
Library of Congress Prints and Photographs Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Card index to the collection available in the Library of Congress Manuscript Reading Room.
Reel guide to the microfilm edition available in the Library of Congress Manuscript Reading Room.
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Biddle, Nicholas, -- 1786-1844 -- Correspondence; Blair, Francis Preston, -- 1791-1876 -- Correspondence; Bragg, Braxton, -- 1817-1876.; Breckinridge, John C. -- 1821-1875.; Brooke, Francis Taliaferro, -- 1763-1851 -- Correspondence; Brown, James, -- 1766-1835 -- Correspondence; Buchanan, James, -- 1791-1868.; Clay, Henry, -- 1811-1847 -- Correspondence; Clay, Henry, -- 1849-1884 -- Correspondence; Clay, James Brown, -- 1848-1908 -- Correspondence; Clay, John, -- 1775-1829 -- Correspondence; Clay, Lucretia Hart, -- 1781-1864 -- Correspondence; Clay, Porter, -- 1779-1849 -- Correspondence; Clay, Susan Maria Jacob; Clay, Theodore Wythe, -- 1802-1870 -- Correspondence; Clay, Thomas Jacob, -- 1853-1939 -- Correspondence; Clay family; Colton, Calvin, -- 1789-1857.; Erwin, Anne Brown Clay, -- 1807-1835 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Greely. A. W. -- 1844-1935.; Harrison, William Henry, -- 1773-1841 -- Correspondence; Hart. Thomas, -- d. 1808 -- Correspondence; Howgate, Henry W; Hughes, Christopher, -- 1786-1849 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Johnston, Josiah Stoddard, -- 1784-1833 -- Correspondence; Kendall, Amos, -- 1789-1869 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert du Motier, -- marquis de, -- 1757-1834 -- Correspondence; Marshall, Humphrey, -- 1760-1841.; Marshall, John, -- 1755-1835 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Nicholas, George, -- 1754?-1799.; Porter, Peter B. -- 1773-1844 -- Correspondence; Randolph, John, -- 1773-1833.; Rochester, William Beatty, -- 1789-1838 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Sergeant, John, -- 1779-1852 -- Correspondence; Taylor, Zachary, -- 1784-1850 -- Correspondence; Watkins, Elizabeth Hudson Clay, -- 1750-1829 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Wickliffe, Robert, -- 1775-1859 -- Correspondence; Bank of the United States (1816-1836); Liberty Party (U.S. : 1840-1848); Transylvania University; Great Britain. -- 1814 Dec. 24.; United States. -- Army -- History -- War of 1812.; United States. -- Army. -- Cavalry; United States. -- Dept. of State; Whig Party (U.S.); Banks and banking -- Kentucky -- Lexington; Burr Conspiracy, 1805-1807.; Diplomatic and consular service, American -- 19th century; Diplomatic and consular service, American -- Portugal; Elections -- United States; Indians of North America -- Texas; Mexicans -- Texas; Nullification (States' rights); Practice of law -- Kentucky -- Lexington